(untitled) (Sciences & Technologie. C, Biotechnologies, 2004)
There was no statistically significant difference between controls and patients for dietary folate. Also the plasma folate level did not slightly differ between the controls and patients. Patients had higher average homocysteine concentrations than control subjects (p<0.05). A significant relationship was observed in controls between plasma folate concentrations and the homocysteine levels (p=0.01), and the folate questionnaire (p=0.001). We found in controls significant positive correlation between vitamin B12 and vitamin B6 (p=0.05). In patients, vitamin B12 is inversely associated with homocysteine (p=0.05).